Between benefit and risk: how entrepreneurs evaluate corporate investors - Stefanie Weniger; Svenja Jarchow (Journal of Business Economics, 2022)
Start-up growth is inevitably dependent on the provision of external resources. Yet, even though corporate venture capital could be an attractive funding source as it provides financial as well as crucial additional resources, corporate venture capitalists (CVCs) are seen as a two-sided sword by entrepreneurs. We, therefore, investigate entrepreneurs' consideration of potential CVC investors and conceptualize a model of their willingness to approach a CVC investor. Using a conjoint experiment with 1680 investor profiles evaluated by 105 entrepreneurs, we show that entrepreneurs consider the investor's motivation, deal experience, access to firm-specific resources, and long-term financial commitment of funds. However, entrepreneurs' evaluation differs depending on their need for specific resources, as well as their fundraising experience. We thereby highlight entrepreneurs' anticipatory trade-off decisions in the light of resource dependence and help CVC managers to optimize their communication and management efforts to attract the most suitable portfolio companies.
Keywords: M13; L26; G24; 650; Corporate venture capital; Investor attractiveness; Entrepreneurial decision-making; Resource need; Entrepreneurial experience; Conjoint analysis